THE BELIEF IN HANTU IN THE MALAY CULTURE FROM THE PERSPECTIVE OF ISLAM - Amin, Mohd Zohdi; Suliaman, Ishak; Salaeh, Husniyah; Ibrahim, Mohamed Akhiruddin; Nor, Azlina Mohamed (Online Journal of Research in Islamic Studies, 2017)
The belief in “hantu” is the result of animism and dynamism among Malays before the arrival of Hindu, Buddha and Islam. Hantu is portrayed as the incarnation of evil souls wishing to harm humans. This belief is related to the concept of soul existence or “semangat” (essence) in everything including the human body. This ancient belief is integrated into their new religions through adaptation process. After embracing Islam, the belief in hantu is not totally dispelled since its features are similar to that of jinn and shaitan, whose existence are acknowledged in Islam. The belief is also supported by the concept of human soul in the afterlife, where it is deemed as immortal. Hantu is portrayed as the soul of the dead, dwelling in certain places and harming the humans. Based on the analysis of the texts of the Quran and Sunnah, it is found that the soul of the dead could never become hantu, as opposed to the Malays’ belief. It is because the soul of the dead is in barzakh, the impassible barrier between the world and the Hereafter. It is a place where the soul is either rewarded or punished for his or her deeds in the past life. The souls cannot act independently by themselves as they are under the control of Allah. Based on this, the belief in hantu is against the Islamic teachings. This belief is capable in affecting a Muslim’s faith as it indirectly leads to the denial of rewards and punishments in the afterlife.